Optimalisasi Pembelajaran Bilingual Melalui Strategi dan Evaluasi yang Tepat Pada Siswa Sekolah Dasar - Syawarianto, Afrizal; Satika, Marshafenda; ., Yuliana; Aulia, Adis; Anafi, Putri Nur; Widagdo, Arif (Peneliti.net, 2025)
In facing the challenges of globalization and the industrial era 4.0, bilingual learning is an important strategy in improving the competence of elementary school students, especially in English language proficiency. This study aims to examine the right strategies and evaluations in the implementation of bilingual learning in order to optimize the student learning process. The method used is a literature study by examining various scientific sources related to bilingual learning, learning strategies, and evaluation techniques. The results of the study indicate that the success of bilingual learning is influenced by teaching strategies that emphasize vocabulary mastery, the use of interactive learning media, a conducive learning environment, and parental involvement. Appropriate learning evaluation includes aspects of the learning process and outcomes with test and non-test approaches that are contextualized in the use of two languages. Evaluation can also be carried out collaboratively between teachers and schools to ensure the sustainability of the bilingual program optimally. This study concludes that appropriate strategies and evaluations are very important to support the success of bilingual learning which not only improves language skills, but also builds students' self-confidence and readiness in a global context.